KETERAMPILAN TEKNIK PASSING SEPAKBOLA STUDI EMPIRIS PADA SISWA KELAS IX PESERTA EKSTRAKULIKULER SMP NEGERI 1 JATIPURO: Sepakbola, Passing - Kurnia Puji Ramdani; Eko Sudarmanto; Gatot Jariono (Universitas Hamzanwadi, 2026)
The main problem in this study is the low level of soccer passing skills among ninth-grade students participating in extracurricular activities. This study aims to analyze the level of soccer passing skills and identify the factors that influence them. The research method uses a descriptive quantitative approach with a survey design through skill tests. The research population consisted of all 30 ninth-grade students participating in soccer extracurricular activities, and all of them were used as samples (total sampling). The instrument used was the Johnson Soccer Test to measure passing skills within 39 seconds. Data analysis was performed using descriptive statistics, including mean, standard deviation, median, mode, and frequency distribution. The results showed that the average passing skill of students was in the Moderate category with a score of 35.50. A total of 8 students (26.67%) achieved the Very Good category, 9 students (30.00%) the Good category, 12 students (40.00%) the Moderate category, and 1 student (3.33%) the Very Poor category. Factors supporting passing skills include internal motivation, teacher support, and competition experience, while inhibiting factors include limited training frequency, monotonous methods, and inadequate facilities. The conclusion of this study is that the majority of students' passing skills are in the moderate category, thus requiring more structured training interventions, increased training frequency, and varied methods.